Investigation of thermomagnetic properties in Ca3Co2O6 over cryogenic temperature between 0 and 100 K. (2nd November 2021) - Ahmed, Emad M.; Hemeda, O. M.; Alamri, Hatem R.; Elghnam, Sameh M.; Hamad, Mahmoud A.
ABSTRACT: A phenomenological model (PM) is applied to simulate the magnetocaloric effect (MCE) of Ca3 Co2 O6 (CCO). On the basis of PM, MCE parameters of CCO are concluded as results of simulation for magnetization vs. temperature under 5 T magnetic field. The maximum value of absolute value of magnetic entropy change is 2.21 J/Kg.K. The values of full-width at half-maximum, relative cooling power and refrigerant capacity are 64 K, 141 and 101 J/Kg, respectively, finding that CCO is a prospective material in magnetic refrigeration (MR) over cryogenic temperature between 0 and 100 K. CCO sample could work as an adequate magnet in MR with limited eddy and little loss of hysteresis. Thus, magnets like CCO sample can do a significant role in the fabrication of various eco-friendly devices. It is recommended that CCO sample is a significant and promising magnet in MR for liquefying nitrogen gas.